A large accretion disc of extreme eccentricity in the TDE ASASSN-14li. Issue 3 (27th July 2018) - Cao, R; Liu, F K; Zhou, Z Q; Komossa, S; Ho, L C
ABSTRACT: In the canonical model for tidal disruption events (TDEs), the stellar debris circularizes quickly to form an accretion disc of size about twice the orbital pericentre of the star. Most TDEs and candidates discovered in the optical/ultraviolet have broad optical emission lines with complex and diverse profiles of puzzling origin. Liu et al. recently developed a relativistic elliptical disc model of constant eccentricity in radius for the broad optical emission lines of TDEs and well reproduced the double-peaked line profiles of the TDE candidate PTF09djl with a large and extremely eccentric accretion disc. In this paper, we show that the optical emission lines of the TDE ASASSN-14li with radically different profiles are well modelled with the relativistic elliptical disc model, too. The accretion disc of ASASSN-14li has an eccentricity 0.97 and semimajor axis of 847 times the Schwarzschild radius ( r S ) of the black hole (BH). It forms as the consequence of tidal disruption of a star passing by a massive BH with orbital pericentre 25 r S . The optical emission lines of ASASSN-14li are powered by an extended X-ray source of flat radial distribution overlapping the bulk of the accretion disc and the single-peaked asymmetric line profiles are mainly due to the orbital motion of the emitting matter within the disc plane of inclination about 26° and of pericentre orientation closely toward the observer. Our results suggest that modelling the complex line profiles is powerful in probing the structures of accretion discs and coronal X-ray sources in TDEs.